Okay I am hoping I know wtf is going on with this question.
The conclusion introduces: A (we discover sentient beings exist) --> C (Sentient Beings =Human Intel).
There is a premise: B(Sentient beings communicate with us)-->C (Sentient Beings = Human Intel)
There is a fact: No spaceship.
Is the key to this problem just figuring out a way to make A (we discover SB exist) flow towards C (Sentient Beings = Human Intelligence)? ...Even if I don't get wtf this argument is saying is that all I need to do for questions similar to these?
If so, is the correct answer choice requiring us to do something of this sort ------------ ~B(NOT Sentient beings communicate with us) --> ~A[(NO SPACESHIP -->(we CANT discover SB exist)
Making it ( A-->B-->C) Therefore: A-->C. If this is what we are doing here, why doesn't A in the conclusion match up to variable A in the answer choice? Why does it not say -- (we discover SB exist --> Spaceship) --> Sentient beings are intelligent as we are.
2 posts • Page 1 of 1